Arrhenius plots for Li-ion battery ageing as a function of temperature, C-rate, and ageing state – An experimental study - Kucinskis, Gints; Bozorgchenani, Maral; Feinauer, Max; Kasper, Michael; Wohlfahrt-Mehrens, Margret; Waldmann, Thomas (Elsevier, 2022)
We present an extensive analysis of Li-ion battery ageing via Arrhenius plots. The V-shaped Arrhenius plots show minima at an optimum temperature corresponding to the longest cycle-life. The V-shape of the Arrhenius plots signifies the crossover between the two dominating ageing mechanisms – solid electrolyte interphase (SEI) growth in the high temperature range and lithium deposition in the low temperature range. Subjects of our investigations are commercial 5 Ah high energy 21,700-type cells with LiNi0.90Co0.05Al0.05O2 + LiNiO2 (NCA + LNO) cathode and Si/graphite anode (∼3% Si) and 0.1 Ah lab-made pouch cells with LiNi1/3Mn1/3Co1/3O2 (NMC111) cathode and a graphite anode. The results of the Arrhenius plots are analysed in the context of C-rate, cell ageing, and electrode properties. We find that the crossover between the dominating ageing mechanism and hence the optimum operating temperature of the Li-ion cells depend on C-rate, anode coating thickness/particles sizes, the state of health, and the shape of the capacity fade curve. Considering the change of the dominant ageing mechanism can help designing battery systems with longer service life. Additionally, we show a lifetime estimation for temperature dependent cycling of batteries emphasizing the merit of Arrhenius plots in the context of battery cell ageing. --//-- Gints Kucinskis, Maral Bozorgchenani, Max Feinauer, Michael Kasper, Margret Wohlfahrt-Mehrens, Thomas Waldmann, Arrhenius plots for Li-ion battery ageing as a function of temperature, C-rate, and ageing state – An experimental study, Journal of Power Sources, Volume 549, 2022, 232129, ISSN 0378-7753, https://doi.org/10.1016/j.jpowsour.2022.232129. Published under the CC BY licence.
Gints Kucinskis acknowledges Latvian Council of Science project “Cycle life prediction of lithium-ion battery electrodes and cells, utilizing current-voltage response measurements”, project No. LZP-2020/1–0425. Institute of Solid-State Physics, University of Latvia as the Centre of Excellence has received funding from the European Union's Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. ZSW acknowledges funding of the project GradiBatt by the industrial collective research programme (IGF no. 20884 N/2) which was supported by the German Federal Ministry for Economic Affairs and Climate Action (BMWK) through the AiF (German Federation of Industrial Research Associations eV) and of the projects RollBatt (03XP0245A) and CharLiSiKo (03XP0333A) funded by the German Federal Ministry of Education and Research (BMBF).
Keywords: Li-ion batteries; Ageing mechanisms; Arrhenius plots; Life-time estimation; Lithium deposition; SEI growth